Impact of Climate Change on Priority Plant Species Conservation in The Forests Under ONAB (the National Wood Office of Benin) Management - M. Deguenon, S. Donalde Dolorès; Idohou, Rodrigue A.; Akpona, T. Jean-Didier; Azihou, Fortuné; Assogbadjo, E. Achille; Sinsin, Brice (European Scientific Journal, ESJ, 2021)
The sustainable conservation of forest resources in a context of climate change and population growth would be compromised in their current form of exploitation by rural communities. The objective of this study is to assess the impact of climate change on the dynamics of habitats favorable to species of conservation priority in the forests under ONAB management as these species are heavily used by the populations living along the shores of these forests. The study will consist of: Khaya senegalensis, Afzelia africana, Khaya grandifoliola, Pterocarpus erinaceus, Anogeissus leiocarpa, Milicia excelsa, Albizia zygia, Vitex doniana, Antidesma laciniatum and Bombax costatum. Techniques based on the principle of maximum entropy (Maxent) combined with GIS were used to project the favorable habitats of these ten species under current and future climatic conditions (Horizon 2050). Species occurrence data were collected and combined with bioclimatic data derived from the Worldclim database and the edaphic (soil) variable. Two climate models were used for future projections (CNRM-CM5, HadGEM-ES models) under the IPCC A2 scenario, and the partial ROC approach was used for the evaluation of the predictions of ecological niche models. Variables such as cec2 (cation exchange capacity, horizon 5-15cm), bio17 (precipitation of the driest quarter), bio12 (annual precipitation), bio3 (isothermality), bio6 (minimum temperature of the coldest month) and bio7 (annual thermal amplitude) were found to be the most relevant respectively for the distribution of Khaya grandifoliola, Albizia zygia, Anogeissus leiocarpa, Antidesma laciniatum, Afzelia africana and Khaya senegalensis. Under current conditions, only 7% of the Beninese territory would be very favorable to the conservation of Khaya senegalensis and the CNRM-CM5 model predicts an increase of 27.5% and 13.2% respectively of these very favorable and moderately favorable areas by 2050 through conversion of unfavorable areas (7.4%). On the other hand, this model predicts an opposite trend at the level of Afzelia africana where it predicts a decrease of 8.1% and 1.8% respectively of the very favorable and moderately favorable areas and an increase of 5.1% of the unfavorable areas. Ecological niche modeling has basically revealed the conversion of some currently unfavorable habitats into very favorable habitats for conservation (this is the case of Khaya grandifoliola, Khaya senegalensis and Vitex doniana) and the extension of some habitats unfavorable to conservation (Anogeissus leiocarpa, Bombax costatum, and Pterocarpus erinaceus) by 2050. This study provides scientific support for planning and is a decision support tool for the conservation of these species at the socio-economic level.